Terkendalanya Proses Pembelajaran Yang Dihadapi Oleh Mahasiswa Dampak Dari Covid-19 - Istiqamah Pebrina; Bagas Aldi Maulana (Fakultas Tarbiyah dan Keguruan, 2021)
This study aims to find out how much obstacles faced by students since the learning system changed due to the impact of covid-19. However, what happens if the obstacles faced by students have a big impact when constrained attending online lectures, of course it will be very influential for these students when they cannot attend lectures with the material given or explained by the lecturer. So how much impact is caused by this type of virus, which causes detrimental to students. From the results of objective research, many students complain about changes in the learning system that cause a decrease in their interest in learning due to constraints and limitations of facilities and infrastructure for students who conduct research. With this research, it is hoped that we can find out how big the impact of Covid-19 is for students.